Enhancing User Interface & User Experience on Digital Learning Platforms Through a Design Thinking Approach - Ridwan Setiawan; Nadia Fitriani; Muhammad Rikza Nashrulloh (Center for Research and Community Service, Institut Informatika Indonesia (IKADO) Surabaya, 2025)
Thinkoguru is an educational platform under development. This study redesigns its user interface and user experience using the Design Thinking framework through five stages: empathize, define, ideate, prototype, and test. User needs were elicited through interviews, synthesized into personas and pain points, and mapped to information architecture, user flows, and a cohesive design system. The outcome is a high-fidelity prototype based on a role-based dual-platform architecture, consisting of a mobile application for learners and a web dashboard for mentors. This paper presents and evaluates the web prototype, which was tested with fifteen participants using the System Usability Scale and achieved an average score of 85.5 (Grade A), indicating excellent perceived usability. The study contributes a clear separation of roles to clarify tasks and reduce cognitive load, together with a traceable linkage from user needs to design decisions that support reuse. These findings provide a structured foundation for the continued development of Thinkoguru and for improving the learning experience on similar educational platforms.